Is COVID-19 infection decreasing the sports performance of the volleyball players? A pilot study - Orscelik, A.; Kaya, I.; Karaaslan, B.; Agiragac, B.; Ceyhan, C. (Journal of Men`s Health, 2021)
Background: Coronavirus (COVID-19) infection has made restrictions on every sports level, from the audience to athletes worldwide. Volleyball players' life were affected by COVID-19 infection, the layout of training, and competitions. This study aims to show the effect of COVID-19 infection on the performance of volleyball players. Methods: Nineteen volleyball players aged 15-20 in the same volleyball club and infected with COVID-19 in the first league of their country were included in the study. Weight, height, fat percentage, muscle mass, countermovement jump, Squat jump, Spike jump tests, and agility T-tests records were compared before (1 and 2 measures) and after the COVID-19 infection (3 and 4 measures). The team physician asked and recorded the players' feelings about changes in their sports performance after the COVID-19 infection. Results: The mean number of PCR (+) days was 13.4 ±2.6. All the median differences of the vertical jump tests had a statistically significant increase at every measure except for the Countermovement jump and squat jump' last two measures, squat jump' first two measures, and spike jump' between twice and third measures. The median differences between the first and last agility T-tests were not statistically significant (p = 0.277). The feeling of volleyball players about the sports performance level was decreased by 57.9%, increase 10.5%, no change 31.6%. Conclusions: Volleyball players' vertical jump performance was getting better despite the COVID-19 infection in our study. Inactivity might be more harmful than COVID-19 infection on sports performance.